Robert Triffin a life - Maes, Ivo 1956- (Oxford University Press, 2021)
"This book provides an intellectual biography of Robert Triffin. Triffin (1911-1993) played a key role in the international monetary debates in the postwar period. He became famous with trenchant analyses of the vulnerabilities of the international monetary system (the Triffin dilemma), predicting the end of the Bretton Woods system. Triffin was a child of the interwar period, marked by the Great Depression and the rise of fascism. He became not only an eminent academic but also an influential policy advisor. In the mid-1940s he worked at the Federal Reserve, participating in several monetary reform missions in Latin America. Thereafter, Triffin played an important role in the creation of the European Payments Union. In his later academic life, Triffin put forward proposals for reforming the international monetary system. But because he doubted that they would come to fruition, he also developed plans for regional monetary integration, particularly in Europe, where he became the monetary advisor of Jean Monnet. With proposals for a European Reserve Fund and a European currency unit, he became one of the intellectual fathers of Europe's monetary union. Throughout his life Triffin remained faithful to the ideals of his youth. The young Triffin was indignant about the Versailles Treaty, while the old Triffin fulminated against the Vietnam war. For him, economics was a way to contribute to a better world. He was strongly attached to his independence and the pursuit of a better and more peaceful world. He was a monk in economists' clothing"--
Keywords: Triffin, Robert; Economists / Belgium / Biography; Economists; Belgium; Biographies